Bacillus safensis isolated from white-leg shrimp, Penaeus vannamei in Taiwan with antagonistic activity against common Vibrio pathogens. (September 2022) - Huynh-Phuoc, Vinh; Ly, Thuyen Quyen; Purbiantoro, Wahyu; Ngo, Hoang Viet Trinh; Afonso, Fernando; Vu, Ngoc Ut; Cheng, Ta-Chih
Abstract: Pathogenic Vibrio species have been notified as the main reason for mass mortality in marine aquaculture. In recent decades, the application of beneficial bacteria with antagonistic activity as probiotics has been chosen to be a promising disease prevention method which contributes significantly to antibiotic use reduction. In the present study, ten shrimps from a co-culture pond with red tilapia were collected to screen for Bacillus bacteria with antagonistic activity against four main Vibrio pathogenic species namely Vibrio parahaemolyticus, V. harveyi, V. alginolyticus, and V. vulnificus . Within 398 isolates, only 8 isolates showed clear activity against all four tested Vibrio spp. All 8 isolates were identified and confirmed to be the same species Bacillus safensis by using both 16S-rRNA and gyrB gene sequences and the BLAST tool. The most potent isolate VQV8 with the highest antagonistic activity was selected for studying common biological characteristics, growth in different conditions, hemolytic activity and antibiotic assessment activity. The results indicated that Bacillus safensis VQV8 grew better at the temperature of 25–37 °C. It could tolerate wide ranges of salinity and pH. This strain was found with high antagonistic activity on the tested Vibrio spp. Bacillus safensis strain VQV8 was found to be a non-hemolytic strain and highly sensitive to most tested antibiotics. Hence, our results suggested that Bacillus safensis strain VQV8 is a safe strain for probiotic purposes and a potent candidate for Vibrio disease prevention in white-leg shrimp culture. Highlights: Bacillus safensis was isolated and identified from the gut of white-leg shrimps B. safensis strain VQV1 – 8 showed strong antibacterial activity on Vibrio spp. B. safensis strain VQV8 was confirmed a safe and potential probiotic bacteria strain